Viral and microbial genotyping by a combination of multiplex competitive hybridization and specific extension followed by hybridization to generic tag arrays - Gharizadeh, Baback (Oxford University Press, 2003)
Detection and identification of microbial pathogens are important for disease diagnosis, treatment and prophylaxis measurements. By introducing an innovative technique, we show a robust, reliable and accurate microarray-based method for identification of microbial pathogens. The technique utilizes a unique combination of multiplex competitive hybridization, which enhances hybridization accuracy of oligonucleotides to the specific target, and apyrase-mediated allele-specific extension, which improves specific extension. As a model system, different clinically relevant human papillomaviruses were selected for this study. The method generated accurate results and proves to be promising for specific and correct microbial and viral typing.